Seasonality and smallholder market participation in Malawi: A baseline report - Van Campenhout, Bjorn; Nabwire, Leocardia (International Food Policy Research Institute, 2022)
Smallholder farmers in low and middle income countries often sell the bulk of their marketable surplus immediately after the harvest, when prices are at their lowest. As part of a field experiment that tests the effectiveness of both income and expenditure planning to nudge farmers into delaying sales of cash crops, we collected detailed information about market participation from a sample of about 3,500 semi-subsistence farmers in Malawi. In this report, we use this data to describe the situation at baseline, before the intervention was implemented. The focus is on three crops that are (also) important to obtain cash. We provide a detailed account of sales transactions in 2021 and also inquire about price expectations in the near future. We also provide suggestive evidence that prices obtained in the past influence price expectations.